FluDen Primer DB –PCR Primer Database for Influenza A and Dengue Virus - Krishnappa, Raghavendra; Paramasivam, Rajendran (International Journal of Biotechnology for Wellness Industries, 2015)
FluDen Primer Database (http://www.fludenpdb.com) has been designed and developed as a web application program to provide free access to the in-silico designed multiple potential primers for PCR detection and quantification assays for Influenza and dengue viruses. This program also permits user to submit sequence of their choice for primer design. The database contains primer records for Influenza and dengue viruses which cause infection in Humans. As of 2014 there are 142 primer sets for screening 32 genes/regions of Influenza and dengue viruses together. Application contain gene information, assay details such as oligonucleotide sequence, primer properties and reaction conditions, publication information. We have developed a resource, FluDen Primer DB which contains primer that can be used for PCR under provided amplification conditions for each primer pair. A distinguish feature of the FlueDen is the primers listed in DB are the products of PCR design application which are experimentally validated. Primers for the FluDen were designed using current genomic information available from the National Center for Biotechnology Information (NCBI).